An Examination of Bullying Tendencies and Bullying Coping Behaviors among Adolescents - Yuksel-Sahin, Fulya (ELSEVIER SCIENCE BV, 2015)
The study aims to examine bullying tendencies and bullying coping behaviors among adolescents in terms of different variables such as gender, participation in social activities, watching violent movies, being submissive, and the presence of the school counselor's activities about prevention of bullying. The study was conducted with 402 high school students. The Bullying Tendency Scale, Coping with Bullying Scale, and Personal Information Form were used to obtain data. The collected data were analysed by MANOVA and t-test. The results of the study revealed that the scores for bullying, bullying tendency, and coping with bullying significantly differed with gender, paticipation in social activities, watching violent movies, being submissive, and the presence of the school counselor's activities about prevention of bullying. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Bullying; Bullying Tendencies; Adolescents; Victim; SCHOOL-CHILDREN; Education & Educational Research